Cold adaptation strategies and diversity of Antarctic bacteria - Gilbert, Jack Anthony (2002)
Bacteria have been isolated from virtually every environment on Earth. The Antarctic continent is no exception. In this extremely cold and dry environment bacteria have colonised various refugia and have evolved a number of strategies for coping with the extreme physico-chemical fluctuations they are exposed to within the environment. These psychrophilic adaptations include cold adapted proteins and lipids which are interest for biotechnology in areas such as frozen foods, agriculture and cryogenic storage. One type of cold adapted protein of particular interest is the antifreeze protein (AFP) for its recrystalisation inhibition and thermal hysteresis activity. It was first isolated from Antarctic fish in the 1970, but has since been found in plants, fungi, insects and bacteria.